ANALISIS FAKTOR BIOMOTOR DAN PSIKOMOTOR DOMINAN PENENTU KEMAMPUAN GROUNDSTROKE FOREHAND TENIS LAPANGAN - Roy Try Putra; Kiyatno -; Siswandari - (Universitas Muhammadiyah Semarang, 2017)
The purpose of study is to find out the dominant factors of biomotor and psychomotor determining tennis groundstroke forehand ability. The research methods were using a quantitative approach and confirmatory factor analysis design. The data collection was processed and analyzed by using Statistical Program Computerized system with SPSS (Statistical Product and Service Solutions) Version 23 and try-out Kaiser-Meyer-Olkin and Bartlett's Test. The population in this study was 40 students of coaching achievement tennis FKIP UNS Surakarta. The sampling technique was purposive sampling. Data collection techniques applied the test and measurement. The results of study as follows: biomotor and psychomotor factors that determine the tennis ability of forehand groundstrokes on having components value factor ? ?0,5? is : grip strength with the factors component value of (0.84), flexibility with the factors component value of (0.34), limb muscle power by the factors component value of (0.82), speed with the factors component value of (0.91), cardiovascular endurance the factors component value of (0.79), hand-eye coordination with the factors component value of (0.50), agility with the factors component value of (0.79). The conclusion of study as follows: biomotor and psychomotor were the most dominant factors determining the forehand groundstrokes ability. Biomotor factors are the speed with the value (0.91) and psychomotor factors are the agility with the value (0.79). Keywords: Biomotor, psychomotor, tennis forehand groundstrokes ability